PERANCANGAN DAN IMPLEMENTASI APLIKASI ONLINE JASA BELLA WEDDING PLANNER BERBASIS WEB - Sayuti, Akhmad; Rahmika, Bella; Davizan, Serry; Irwansyah, I (Program Vokasi Universitas Negeri Gorontalo, 2025)
The rapid growth of information technology has encouraged many sectors, including wedding planning services, to adopt digital systems to improve efficiency and quality of service. Bella Wedding Planner is a wedding service provider that requires a web-based information system to facilitate the management of client data, event schedules, and the delivery of service information online. The purpose of this study is to implement a web-based online application that can help Bella Wedding Planner manage its services efficiently. The system development method applied is the Waterfall method, which consists of the analysis, design, implementation, testing, and maintenance phases. The results of the implementation show that this application functions to facilitate the ordering process, communicate with clients, and manage event data centrally. Thus, this system is expected to improve the professionalism and competitiveness of Bella Wedding Planner in the digital era. Wedding Organizer services play a role in helping couples who are getting married and their families plan their wedding events. The popularity of this service arises because of the ease of planning a wedding. However, there are obstacles in promoting wedding services, which often face problems such as incomplete wedding package information and manual transaction data processing, which has the potential to cause errors. This study shows that the Wedding Organizer application can provide complete information about wedding packages, update the latest package list, manage transactions in real-time, and automatically process order information. This study uses the waterfall method which includes the steps of analysis, implementation, testing, and maintenance. Data collection is done by collecting information about wedding packages, photo galleries, and vendor data. The programming language used in this project is PHP, with MySQL functioning as the Database Management System (DBMS).